Language-specific Differences in Online Reviews – Case of Fine-dining Prague Restaurants - Kvitkova, Zuzana (Turizam, 2019)
Word-of-mouth is an important factor in all phases of the purchase decision-making process. As the web 2.0 came in, online reviews platforms grew up and started significantly influencing the travel behavior in the last years, including gastronomy. The largest platform is Tripadvisor.com. With respect to worldwide usage and importance of Tripadvisor.com in the tourism sector, this was chosen as a base for the research of restaurant reviews. This study aims to identify whether there are differences in the satisfaction level with the restaurants between language groups. Prague is the top highlight of the tourism offer of the Czech Republic. The capital is also a leader in regards of quality and luxury services, gastronomy is no exception. According to Tripadvisor.com there are almost 120 restaurants offering fine dining and most of them offer a good quality according to the reviews. This type of restaurants for the high-end customers was analyzed to identify the most demanding language groups and the less critical language groups. The German, Spain, Italian, French and Czech language were analyzed. With some limitations we can assign the language to a nationality. The average evaluation for each language is calculated and the statistical tests are made to confirm the findings.